2017
DOI: 10.1080/24749508.2017.1332860
|View full text |Cite
|
Sign up to set email alerts
|

Remediation techniques applied for aqueous system contaminated by toxic Chromium and Nickel ion

Abstract: Heavy metals contamination in environment is a global problem. Environment is polluted by different toxic metals due to industrial sources and anthropogenic activities. Variety of methodologies has been applied for the purification of waste water. Thus, article mainly focuses on the current developments and applicability of various wastewater treatment techniques, i.e., adsorption, membrane filtration, ion exchange, electrochemical treatment and electrocoagulation. Also, development of new adsorbents especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Where Kth, is the Thomas constant (mL/min-1 mg-1); qo, is the maximum solute concentration in the solid phase (mg/g); X, is the amount of adsorbent in the column (g), Q is the flow rate (mL/min) and V (L) is the volume of the effluent at the time of operation [9].…”
Section: Thomas Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Where Kth, is the Thomas constant (mL/min-1 mg-1); qo, is the maximum solute concentration in the solid phase (mg/g); X, is the amount of adsorbent in the column (g), Q is the flow rate (mL/min) and V (L) is the volume of the effluent at the time of operation [9].…”
Section: Thomas Modelmentioning
confidence: 99%
“…Nickel is widely used in production of batteries, steel, alloys, and prolonged exposure to it can cause stomach aches and carcinogenic effects on the blood, kidneys, or chronic bronchitis and alteration of the lung [3]. These metals are bioaccumulative, are magnified in the food chain and are resistant to degradation [8]; therefore, different techniques have been implemented for the removal of heavy metals in solution such as: oxidative techniques, filtration and ultrafiltration, membrane extraction, ion exchange, among others [9], [10]. However, the application of these technologies is expensive due to operational and energy costs, C labor; in addition, they generate toxic waste sludge and have little efficiency at trace concentration levels [11].…”
mentioning
confidence: 99%
“…But, the later increase in degradation was smaller in range compared to the first showing that the effect of photocatalyst concentration on the degradation efficiency has slowed down. This is because the increased amount of photocatalyst blocks the light from reaching some of the particles which makes some of the photocatalysts surfaces unavailable for light absorption, which indicated that it has approached the optimum concentration of photocatalyst [16,21,22].…”
Section: Variables Effect On the Degradation Efficiency Of Methylene Bluementioning
confidence: 99%
“…Breathing Cr (VI) over a long period increases the risk of lung and nasal cancer. Studies show that the presence of these in drinking water can cause an increased risk of stomach cancer and reproductive harm [10][11].…”
Section: Introductionmentioning
confidence: 99%